Preliminary study on the diversity and abundance of Onthophagus species in Kg. Beting, Kuala Pilah / Nur Izati Shamsir - Shamsir, Nur Izati (2019)
Clear understanding on the links between ecological functions and biodiversity is need to be assessed and predicted the true environmental consequences of human activities. Feces that produces from the feeding process, dung beetles involve in the ecosystem functions ranging from secondary seed dispersal for nutrient cycling and parasite suppression. The objective of this study is to determine the diversity and abundance of Onthophagus spp. in Kuala Pilah, Negeri Sembilan and to identify the diversity and abundance of Onthophagus spp. nocturnal and diurnal. Pitfall trap has been used to capture this species. Soap water is used to reduce the water retention. Rotten fish is used as a bait to attract Onthophagus spp. A total of 136 individuals of Onthophagus spp. were successfully caught in rubber plantation and forest at Kg. Beting, Kuala Pilah. Improvements of this research can be implemented if the length of time is extended and the replication of sample quotes can be increased.